THE EFFECT OF GENDER DIFFERENCES, AUDIT FEES, AUDIT WORK EXPERIENCE, AND INDEPENDENCE ON AUDIT QUALITY - Utama, Fikri Rizki; Islam, Maruful (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
Public accountants (APs) are required to maintain Audit Quality (KA) to produce financial statements (LK) that meet predetermined standards. Therefore, this study aims to determine the influence of gender differences, audit fees, audit work experience, and auditor independence on financial statements. The study procedures were carried out using a survey method, and the sample population was selected with convenience sampling by taking the condition of public accountants who work at KAP in Bandar Lampung City. Data were obtained using a questionnaire and then processed with the SPSS program. The results showed that audit work experience and auditor independence had a significant influence on KA. However, gender differences and audit fees had no significant effect.